(untitled) (Asian Business Research, 2022)
This article is intended to reach peak carbon policy as the breakthrough point, to adopt new energy automotive industry is an important part of the carbon amount to peak strategy this conclusion, and with the company as the research object, by adopting division of the valuation method and price-to-sales ratio valuation method to estimate the company eventually concluded that carbon reach peak policy analysis on the influence of the automobile manufacturing company valuations and make relevant summary.